MANAJEMEN TRANSFORMASI DIGITAL PENDIDIKAN SEKOLAH DASAR DI KABUPATEN SINTANG - Parida, Lusila; Serani, Gabriel; Andri, Andri; Dike, Daniel (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The independent curriculum as one of the digital development products developed through the independent learning platform has become a challenge for the education field, including in Sintang Regency. This study aims to describe the management of digital transformation of education in the Implementation of the Independent Curriculum (IKM) in Sintang Regency. The research method used is case study research. Data collection techniques aimed of mapping the readiness of schools, teachers, students, parents in utilizing ICT, the Independent Teaching Platform. The results show that digital transformation management of education has been implemented at Elementary Schools in Sintang Regency. In the planning aspect, it is done by mapping priorities in the short, medium and long term. Assessing and analyzing capabilities, requirements, challenges and opportunities related to digital transformation. Building steps and synergy with various related parties to achieve goals. Socializing the program and setting achievement targets in digital transformation management. In terms of implementation, it is to apply the entire series of planning by directing, playing an active role from structural and functional to influence and strive for all stakeholders to be able to implement the digital transformation program in the Implementation of the Independent Curriculum effectively and efficiently. Meanwhile, monitoring or evaluation of the digital transformation program is the result of the achievement of the planning and implementation process, namely 65.35% of IKM achievement so that it can be used as a benchmark for success or as a follow-up effort for the program at Elementary Schools in Sintang Regency.